THE RHETORIC OF THE UAE'S MIDDLE EAST CIVILIZATION ADVANCEMENT TO THE SURROUNDING NATURAL ECOSYSTEM - Subhan Jaelani (Arabic Literature Department, 2021)
The Middle East is side by side with western countries competing in optimal utilization in processing the resources provided by the earth. Clean water is an absolute source of life that humans need. In addition, the technology and wealth of a country are the benchmarks for supporting the achievement of a country's goals. The use of manipulated nature to meet the needs of clean water is the idea of one of the developed countries in the Middle East, namely the United Arab Emirates. The United Arab Emirates, which is rich in natural wealth and abundant wealth, accompanied by advances in mindset and technology that is never separated from commemorating its culture, makes them think more deeply than other countries with their wealth of clean water. The sowing of salt in the atmosphere along with desalination/filtration of seawater into ready-to-consume water is an action taken by the Emirate to meet the needs of its people. Changes in natural ecosystems that were originally arid to become barren and green are almost impossible actions but have been successfully carried out and implemented by developed countries in the Middle East. Then the question arises about whether changing the shape and manipulating nature that should be as usual in this ecosystem will have an impact or benefit the general public.